Transcription factor p63 regulates key genes and wound repair in human airway epithelial Basal cells - Warner, S.; Hackett, T.; Shaheen, F.; Hallstrand, T.; Kicic, Anthony; Stick, S.; Knight, D. (American Lung Association, 2013)
The airway epithelium in asthma displays altered repair and incomplete barrier formation. Basal cells are the progenitor cells of the airway epithelium, and can repopulate other cell types after injury. We previously reported increased numbers of basal cells expressing the transcription factor p63 in the airway epithelium of patients with asthma. Herewesoughttodetermine themolecular consequencesof p63 expression in basal human airway epithelial cells during wound repair. Because at least six isoforms of p63 exist (N-terminally truncated [Î”N] versus transcriptional activation promoter variants and Î±, Î², or Î³ 3' splice variants), the expression of all isoforms was investigatedinprimaryhumanairwayepithelialcells(pHAECs). Wemodulated p63 expression, using small interfering RNA (siRNA) and adenoviral constructs to determine the effects of p63 on 21 candidate target genes by RT-PCR, and on repair using a scratch wound assay. We found that basal pHAECs from asthmatic and nonasthmatic donors predominantly expressed the N-terminally truncated p63Î± variant (Î”Np63Î±) isoform, with no disease-specific differences in expression. The knockdown of Î”Np63, using specific siRNA, decreased the expression of 11 out of 21 genes associated with epithelial repair and differentiation, including Î²-catenin, epidermal growth factor receptor, and Jagged1. The loss of Î”Np63 significantly inhibited wound closure (which was associated with the decreased expression of Î²-catenin and Jagged1), reduced epithelial proliferation as measured by Ki-67 staining, and increased E-cadherin expression, potentially preventing cytokinesis. In conclusion, Î”Np63Î± is the major isoform expressed in basal pHAECs, and is essential for epithelial wound repair. The role of Î”Np63Î± in epithelial barrier integrity requires further study to understand its role in health and disease. Copyright Â© 2013 by the American Thoracic Society.